Strategi Pembelajaran Pendidikan Agama Islam Dalam Membentuk Kualitas Spiritual Dan Intelektual Siswa MTs Muhammadiyah Ngestiboga Ii Kecamatan Jayaloka Kabupaten Musi Rawas Sumatera Selatan - Latif Yusuf Arifin; Hery Noer Aly; Ahmad Suradi (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2023)
This research aims to analyze Islamic Education Learning Strategies in Forming Students' Spiritual and Intellectual Qualities at MTs Muhmmadiyah Ngestiboga II. The research method used in this research is a qualitative descriptive method. The formulations of the problem in this research are: First, what is the Islamic Religious Education Learning Strategy in shaping the spiritual and intellectual qualities of students at MTs Muhammadiyah Ngestiboga? Second, what are the supporting factors in implementing Islamic education learning strategies in shaping the spiritual and intellectual qualities of students at MTs Muhammadiyah Ngestiboga II? Third, how to overcome the obstacles faced in implementing Islamic religious education learning strategies in shaping the spiritual and intellectual qualities of students at MTs Muhammadiyah Ngestiboga II? Data collection techniques in this research are observation, interviews and documentation. The results of the research show that the Islamic Religious Education Learning strategies in forming the spiritual and intellectual qualities of MTS Muhammadiyah Ngesuboga II students are the Dhuha and Midday Prayer Agenda in congregation, Cultivating Exemplary Practice, Cultivating Murojaah Discipline in Reading the Al-Quran Before Starting Lessons, and Controlling teachers and homeroom teachers through daily agenda book. Supporting factors for the Islamic Religious Education Learning Strategy in Forming the Spiritual and Intellectual Qualities of Students at MTs Muhammadiyah Ngestiboga II Village, and how to overcome the obstacles faced in implementing Islamic religious education learning strategies in forming the spiritual and intellectual qualities of students at the MTs Muhammadiyah Ngestiboga II School, namely lack of personnel educators who can hinder the process of implementing student learning strategies at the Mts Muhammadiyah Ngestiboga II school. Steps to overcome these obstacles have been formulated jointly by the school. The final results of this activity need to be improved and reviewed to what extent the level of success has an impact on students, especially in terms of students' spiritual and intellectual aspects.